Preferences for the Integration of Mathematics and Islam: A Systematic Literature Review - Zainal, Nur Fitriani; Satriani, Satriani (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This paper is a systematic literature review that aims to describe the thematic preferences of articles discussing the integration of mathematics and Islam published in Indonesian journals. The data were obtained from scientific journal articles retrieved through a search of mathematics education journals accredited at SINTA 1 and SINTA 2 using a systematic literature review procedure. A total of 56 articles were identified from these accredited journals. The search process applied predefined inclusion and exclusion criteria, keyword-based screening, and full-text eligibility checks. Most publications originated from journals affiliated with universities that uphold religious values. The dominant research approach employed was Research and Development (R&D). The most common educational levels examined were Junior High Schools (SMP) and Islamic Junior High Schools (Madrasah Tsanawiyah/MTs). The topics of integration between mathematics and Islam predominantly centered on Islamic-integrated mathematics learning. These findings offer valuable guidance for educators, curriculum developers, and researchers in designing mathematics learning aligned with Islamic values and in enhancing culturally responsive mathematics education in Indonesia. This study also provides a systematic mapping of research on the integration of mathematics and Islam in SINTA-accredited journals, outlining the current state of the field and offering a comprehensive foundation for more diverse and robust future research in Islamic-integrated mathematics education.